2022
DOI: 10.4049/immunohorizons.2100105
|View full text |Cite
|
Sign up to set email alerts
|

Durable Immunity to Ricin Toxin Elicited by Intranasally Administered Monoclonal Antibody–Based Immune Complexes

Abstract: Inhalation of ricin toxin (RT) elicits profuse inflammation and cell death within the upper and lower airways, ultimately culminating in acute respiratory distress syndrome. We previously reported that the effects of pulmonary RT exposure in mice are nullified by intranasal administration of an mAb mixture consisting of PB10, directed against ricin’s enzymatic subunit (RTA), and SylH3, directed against ricin’s binding subunit (RTB). We now report that delivery of PB10 and SylH3 as an RT–mAb immune complex (RIC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…The necessity of T cell help is particularly interesting, as previous work reported endogenous IgG generation within roughly 7 days of i.n. RICs administration [3]. This rapid timeline for a T-dependent adaptive response is unusual, as T cell activation alone can take 24 h [14], and germinal centers (GCs) typically do not begin forming until approximately 4 days after initial antigen exposure [15], with full formation about 7-10 days after antigen encounter [16].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The necessity of T cell help is particularly interesting, as previous work reported endogenous IgG generation within roughly 7 days of i.n. RICs administration [3]. This rapid timeline for a T-dependent adaptive response is unusual, as T cell activation alone can take 24 h [14], and germinal centers (GCs) typically do not begin forming until approximately 4 days after initial antigen exposure [15], with full formation about 7-10 days after antigen encounter [16].…”
Section: Discussionmentioning
confidence: 99%
“…For collection of BALF, 1mL of 0.6mM EDTA in PBS was used to flush the lungs intratracheally before recollection of fluid and storage at -80°C until use. Blood was procured from the submandibular vein and serum isolated as described previously [3]. prior to RICs immunization.…”
Section: Mouse Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, it was confirmed that intranasal RIC administration was more effective than i.p. delivery in inducing immunity against intranasal RT exposure [ 99 ].…”
Section: Current Therapeutic Antibodiesmentioning
confidence: 99%